Teoria crítica e religião no pensamento de Jürgen Habermas: possibilidades e limites da teoria do agir comunicativo no campo teológico-político - Góis Filho, Benjamim Julião de (2020)
This thesis aims at investigating the religious element in the thought and religiosity of Jürgen Habermas in post-metaphysical times, as well as the exploration of the possibilities and limits of his critical theory and discursive ethics in the theological-political field. It is assumed as a research hypothesis the thesis that it is possible to think with Habermas a type of post-metaphysical (agnostic) philosophy of religion within his Critical Theory, not as an end in itself: there are notes, a set of texts/reflections that point to the possibility of thinking aboutreligion. It is a question of highlighting inspirations of an ethical nature, which Habermas collects from religious experiences. There is a fundamental intuition that Habermas inherits from the Hebrew tradition from Schelling, for example, the idea of a God who contracts, shrinks so that the world exists -the idea of an egothat withdraws so that the other exists. Such intuition can be seen in his discursive ethics, in which it is necessary for an “I” (ego) to withdraw in order for an “other” (alter) to express itself, to place itself. It can be seen that as Habermas declares himself,clearly and consistently, not an atheist, but an agnostic, about God as the ultimate reference of religion, nothing can be said, neither affirmed nor denied. Therefore, hisinterest in the discourse about God is strictly ethical. In his post-metaphysical thinking, God is a strong inspiration for what is fundamental in human relationships. Hence the permanent reference in the analysis hemakes of the different authors (Schelling, Martin Buber, Gershom Scholem, and Karl Jaspers, Michael Theunissen,J. B. Metz) to the dialogical relations that complete the core of the human being. The figure of the God who withdraws to make room for the other to remainpresent throughout the course of his thinking. The general objective of thisresearch is to articulate a discussion that demonstrates that there is a philosophy of religion in the sense that Kant thought: a strictly ethical sense. There is a possibility of thinking about a way of doing philosophy of religion in post-metaphysical times, a philosophy of religion "in a post-metaphysical approach", a way practiced, even, by the first obliged theorists of what was called the Frankfurt School. The specific objectives are: a) Thinkingabout the relationship between Critical Theory by Habermas and philosophy, so that the place of philosophy in contemporary times is pointed out; highlighting the extent to which Habermas fits into the Frankfurt School tradition; as well as discussing a criticism made by Puntel to the post-metaphysical thinkingby Habermas; b) Discussinghow Habermas thinks about religion at the turn of the millennium and what are the limits and possibilities of the Theory of Communicative Action in the theological-political field.